Uganda loses USD 271 million annually due to limited investment in leather processing - Private Sector Development Unit Ministry of Finance, Planning and Economic Development (Economic Policy Research Centre, 2021)
Uganda’s leather sector has enormous potential in transforming the livestock sector through providing the necessary jobs, acting as an avenue for import substitution and export promotion. However, the leather sector is faced with limited processing of leather, with over 95 percent of the sector’s exports in raw or semi-processed. This costs Uganda over USD 271 million worth of export revenue. Accordingly, this brief recommends the need to; establish a leather park for all tanneries, promote public-private partnership investments in finished leather processing and establish capacity building programmes to skill leather SMEs (Juakalis) to produce high-quality leather products.